STRATEGI PENGUATAN KOMPETENSI TENAGA NONFUNGSIONAL DI PERPUSTAKAAN BADAN PENGEMBANGAN DAN PEMBINAAN BAHASA KEMENTERIAN PENDIDIKAN DASAR DAN MENENGAH - Raudlatul Jannah, Najwa; Muhamad Taufik Bintang Kejora; Fatimah Az Zahro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze strategies for strengthening the competence of non-functional staff at the Library of the Agency for Language Development and Cultivation, Ministry of Primary and Secondary Education. The research is motivated by the condition that library management and services continue to run despite the absence of an active librarian, while operational duties are carried out by administrative staff with non-library educational backgrounds. This study uses a qualitative descriptive approach through observation, interviews, and documentation. Data are analyzed through data collection, condensation, presentation, and conclusion drawing, supported by SWOT analysis to identify internal and external factors. The analysis shows that staff experience, organizational trust, and service continuity are internal strengths, while limited formal library education and the absence of active librarians are weaknesses. Opportunities include competency standards, training programs, and information technology development, whereas threats include increasing service demands and dependence on certain personnel. The recommended strategies include competency-based training, technical mentoring, work procedure documentation, phased competency mapping, and periodic evaluation. Strengthening competence is expected to improve staff knowledge, skills, work attitudes, and the quality of library services.